The Effect of Inflation, Interest Rate, and Indonesia Composite Index (ICI) to the Performances of Mutual Fund Return and Unit Link with Panel Data Regression Modelling - Siti S. Purwaningsih; Anny Suryani; Euis Sartika (UPT Penerbitan Universitas Jember, 2016)
The financial market investment in Indonesia is growing rapidly, particularly the growth of mutual fund return market and unit link. After the government issued a regulation on Reksadana Kontrak Investasi Kolektif (KIK), the needs of this learning is no longer confined to the institutional investors but it covers wider community. Starting from the development of the financial market investment, the previous studies, and the introductory study conducted by the writers, this study uses several variables; they are inflation, interest rate, ICI, mutual fund returns, and unit link. This study is purposed to analyse the effect of inflation, interest rate, and ICI to the performances of mutual fund return and unit link with panel data. It is also purposed to determine the best regression modelling from panel data which illustrates the linier correlation of inflation, interest rate, ICI and mutual fund returns as well as unit link in order to get the behavioural description and the performancesof mutual fund return and unit link as one of the investment instruments in this modern era. The focused objects are the performance of the products of mutual fund return in the kind of stocks from the investment management firms in Indonesia as well as the performance of the products of unit link in the kind of stocks from life insurance companies in certain year, then the data is called cross section data. Meanwhile, if the focused object is on the time, the data of inflation, interest rate, and ICI as well as the performances of mutual fund return and unit link products in recent yearsis called time series data. The combination of both data, some investment management firms which provide mutual fund return as well as some life insurance companies which provide unit link in Indonesia from 2007 to 2014, is called panel data (pooled data). The result of this study is the best model of mutual fund return and unit link with Fixed Effect (FE) method. The correlation between inflation, interest rate, and ICI to the mutual fund return is 99.30 %. The correlation between inflation, interest rate, and ICI to the unit links is 98.74 %.